Local Government Policies in Discipline Radicalism in Education In Aceh Tamiang - Zainuddin Zainuddin; Mohd Nasir; Samsuar Samsuar; Syamsul Rizal; Nyak Mauliza Warzukni (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2026)
Religious radicalism in dayah educational institutions is a serious challenge to social stability and national ideology in Aceh Tamiang. This study analyzes local government policies in disciplining radicalism in dayah educational institutions using a qualitative approach with case studies. Data was collected through in-depth interviews, observations, and documentation, and then analyzed using the Miles & Huberman model. Michel Foucault's theoretical framework of disciplinary power is used to understand the mechanisms of supervision, normalization, and reward and punishment systems. the epistemological repercussions of state-led deradicalization, suggesting that the disciplinary mechanisms of surveillance and curriculum standardization may engender a nascent knowledge regime, thereby systematically homogenizing religious interpretations. Preliminary findings indicate that such an approach appears effective in mitigating the escalation of radicalism, ostensibly avoiding overt social conflict. This research contributes to the development of inclusive, moderate, and nationally oriented dayah education policies